1999
DOI: 10.1074/jbc.274.19.13594
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NF-κB RelA Phosphorylation and Transcriptional Activity by p21 and Protein Kinase Cζ in Primary Endothelial Cells

Abstract: The activity of the transcription factor NF-B is thought to be regulated mainly through cytoplasmic retention by IB molecules. Here we present evidence of a second mechanism of regulation acting on NF-B after release from IB. In endothelial cells this mechanism involves phosphorylation of the RelA subunit of NF-B through a pathway involving activation of protein kinase C (PKC) and p21 ras . We show that transcriptional activity of RelA is dependent on phosphorylation of the N-terminal Rel homology domain but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 59 publications
8
164
2
Order By: Relevance
“…Previous reports have shown that serum can increase NFκB activity, 36,37 perhaps through serum-activated GTPases, such as Rho 38,39 and Ras. 40 Our data show that serum is sufficient to induce p65 nuclear translocation in MEFs (Fig. 5A and B) and that serum-induced NFκB activation is unaffected by activated Rac.…”
Section: Discussionmentioning
confidence: 74%
“…Previous reports have shown that serum can increase NFκB activity, 36,37 perhaps through serum-activated GTPases, such as Rho 38,39 and Ras. 40 Our data show that serum is sufficient to induce p65 nuclear translocation in MEFs (Fig. 5A and B) and that serum-induced NFκB activation is unaffected by activated Rac.…”
Section: Discussionmentioning
confidence: 74%
“…This in turn suggests that TNFa-induced activation of NFkB is qualitatively di erent from Ras-induced activation of NFkB in this model system, even though other studies have reported that Ras activation mediates or enhances the e ects of TNFa signaling in some cell types (Trent et al, 1996;Anrather et al, 1999). To address the question of whether NFkB serves as an obligate target of Ras signaling to inhibit myogenesis, we began by examining if TNFa-induced activation of NFkB in this system relies on endogenous Ras p21 function.…”
Section: Ikba Expression Does Not Reverse Ras-induced Inhibition Of Smentioning
confidence: 65%
“…The finding that this PKC isoenzyme is involved in SP-A-mediated anti-inflammation was initially surprising because LPS-or cytokine-induced PKC activity was previously shown to induce NF-B activation by distinct mechanisms, as follows: first, through its activation of IKK (52,53), and second, by phosphorylating p65 (45,54). Besides PKC , kinases implicated in p65 phosphorylation include CKII, protein kinase A, IKK2, Akt, p38, p42, and p44 (17).…”
Section: Discussionmentioning
confidence: 99%